Overarching Greek trends in European philosophy - Coronel Ramos, Marco Antonio (IVITRA research in linguistics and literature ;, 2021)
"This book is an enquiry into memory in the Western world. Specifically, memory is the framework of culture, because it links the present to the past--or tradition--and projects it into the future. For this reason, any work focusing on memory involves a double challenge: (1) to reveal the origin of concepts and (2) to glimpse the course of thoughts. This is the case of the present volume, in which the authors make several tastings of Europe's intellectual heritage, by taking into account both the Greek origin of this legacy and its relevance for understanding the European philosophical heritage. In particular, these papers focus on the Aristotelian tradition, the true keystone of Europe, and on other currents of thought that have also played an essential role in the intellectual evolution of the Old Continent. In the latter field, there are contributions, for instance, on philosophical-religious traditions such as Orphism or on certain fundamental aspects of Neoplatonism both in the Classical World and in Christian authors. The volume concludes with various works on the survival of these intellectual trends from the Renaissance to the present day. Consequently, this work offers the opportunity to delve deeper into some of the aspects that define Western civilisation, observed both from its origin and its evolution over the centuries. The volume contains papers in Spanish, Portuguese, Italian, and English."--